Sclerococcum pseudobactrodesmium sp. nov. from a terrestrial habitat in China - Ma, Jian; Liu, Ning-Guo; Tang, Xia; Xiao, Xing-Juan; Chen, Xue-Mei; Xiao, Yuan-Pin; Zhang, Ya-Zhou; Lu, Yong-Zhong; Boonmee, Saranyaphat (Phytotaxa, 2023)
In this study, four terrestrial collections of bactrodesmium-like hyphomycetous fungi were isolated from rotten wood in Guizhou Province, China. Phylogenetic analyses based on the combined LSU, ITS, mtSSU, and SSU sequence matrix indicate that these four isolates represent one species belonging to the Sclerococcum within the Dactylosporaceae, and present a distinct lineage. Therefore, Sclerococcum pseudobactrodesmium sp. nov. was introduced with corresponding morphological descriptions. Sclerococcum pseudobactrodesmium represents the first lignicolous asexual species from a terrestrial habitat.